2013
DOI: 10.1021/jp312421d
|View full text |Cite
|
Sign up to set email alerts
|

FRET Sensitization of Tungsten–Alkylidyne Complexes by Zinc Porphyrins in Self-Assembled Dyads

Abstract: The photophysical properties of self-assembled zinc-porphyrin/tungsten-alkylidyne dyads have been investigated with the aim of determining whether the porphyrin S excited state sensitizes the tungsten-alkylidyne (3)[dπ*] state. The luminescent metalloligand W(≡CC(6)H(4)CCpy)(dppe)(2)Cl (1; dppe = 1,2-bis(diphenylphosphino)ethane) has been synthesized and shown by electronic and NMR spectroscopy to coordinate axially to ZnTPP and ZnTP(Cl)P (TP(Cl)P = tetra(p-chlorophenyl)porphyrin) via the terminal pyridyl grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 96 publications
(156 reference statements)
2
38
0
Order By: Relevance
“…In this context, we recently described the structures, bonding, and excited-state properties of self-assembled zinc-porphyrin/tungsten-alkylidyne dyads, in which the luminescent tungsten-alkylidyne metalloA 1) is coordinated via its pendant pyridyl moiety to the zinc center of a tetraarylporphyrin (Scheme 1). [12] These dyads, generically denoted hereafter as ZnPor(1), were designed to take advantage of the valuable light-harvesting, photophysical, and redox properties of zinc porphyrins. [13] Density-functional theory calculations on ZnPor(1) showed that the HOMO is the redox-active d xy orbital of 1, and that this and most other frontier orbitals are more than 99 % localized on the parent subunit (Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, we recently described the structures, bonding, and excited-state properties of self-assembled zinc-porphyrin/tungsten-alkylidyne dyads, in which the luminescent tungsten-alkylidyne metalloA 1) is coordinated via its pendant pyridyl moiety to the zinc center of a tetraarylporphyrin (Scheme 1). [12] These dyads, generically denoted hereafter as ZnPor(1), were designed to take advantage of the valuable light-harvesting, photophysical, and redox properties of zinc porphyrins. [13] Density-functional theory calculations on ZnPor(1) showed that the HOMO is the redox-active d xy orbital of 1, and that this and most other frontier orbitals are more than 99 % localized on the parent subunit (Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…10 11 s À1 ) to produce the 3 A C H T U N G T R E N N U N G [dp*] state (Figure 1 b). [12] Thus, the ZnPor(1) architecture significantly enhances light harvesting for the photochemically useful 3 A C H T U N G T R E N N U N G [dp*] state of 1.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations